The acquisition of vocabulary through three memory strategies - Pérez, Libia Maritza; Alvira, Roberto (Colombian Applied Linguistics Journal, 2017)
The present article reports on an action research study that explores the implications of applying three vocabulary strategies: word cards, association with pictures, and association with a topic through fables in the acquisition of new vocabulary in a group of EFL low-level proficiency teenagers in a public school in Espinal, Tolima, Colombia. The participants had never used vocabulary strategies to learn and recall words. Two types of questionnaires, a researcher’s journal, and vocabulary tests were the instruments used to gather data. The results showed that these strategies were effective to expand the range of words progressively and improve the ability to recall them. The study also found that these strategies involve cognitive and affective factors that affect students’ perception about the learning of vocabulary. The implementation highlighted the need to train teachers and learners in strategies intended to teach and learn vocabulary and to subsequently include them in the English language program in any school.